Research on Construction Mechanical Behaviour of Connecting Aisle in Shield Tunnel. (June 2018) - Sun, J C; Zhang, H; Peng, T; Xiao, C L
Abstract: Based on connecting aisle of shield tunnel projects in Shenzhen Metro Line 5, in accordance with the complex space structure formed by shield tunnel and connecting aisle, the study chose a three-dimensional numerical model linked by structure and surrounding rock for the calculation and analysis of the stress effect. It showed that due to the connecting aisle construction, the symmetrical deformation of shield tunnel was transformed into unsymmetrical deformation and the crossing segment produced a phenomenon of stress concentration, which caused the production of the upper and lower section of the overall tension of adverse stress form in side opening segment and contact channel structure side themselves. The tension zone of the whole structure was to connect through the lower half of the channel and the surrounding part of segment, so highly attention should be paid to the force structure and waterproof both in design and construction period.